TINJAUAN PENGALAMAN WISATAWAN TENTANG PENERAPAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 DI PANTAI PASIA TIKU KABUPATEN AGAM - Algi Joni Putra; Youmil Abrian (Bogor Hospitality Journal, 2022)
The title of this study is a review of tourist experiences regarding the implementation of health protocols during the Covid-19 period at Pasia Tiku Beach, Agam Regency. The research aims to find out how the implementation of Covid-19 health at Pasia Tiku Beach, Agam Regency. This research was motivated by comments from tourists/visitors who came to Pasia Tiku beach, Agam district. The research population consisted of visitors who visited Pasia Tiku Beach, Agam Regency during the Covid-19 period, with a sample of 100 people using a purposive sampling technique. From the results of the study, the experience of tourists regarding the implementation of health protocols during the Covid-19 period at Pasia Tiku Beach, Agam Regency was quite good with an average score of 60.02 which was in the range of scores 53.34 – 66.66, while based on each The indicators are: (1) Update info regarding Covid-19 is categorized as quite good with an average score of 12.24 which is in the score range 10.67 - <13.33 and a frequency of 54 people with a percentage of 54%, (2) Provision of hand washing facilities is categorized as not good with the average value is 15.13 which is in the score range 10.01 - <13.66 and the frequency is 32 people with a percentage of 32%, (3) The use of protective equipment is categorized as quite good with an average value of 15.25 which is in the range score 13.33 - <16.66 and the frequency is 49 people with a percentage of 49%, (4) Maintaining a minimum distance of 1 meter is in a pretty good category with an average score of 17.40 which is in the range of scores 16 - <20 and a frequency of 54 people with a percentage of 54%.